2017
DOI: 10.3906/mat-1604-20
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous strong proximinality in Banach spaces

Abstract: Several researchers have discussed the problem of strong proximinality in Banach spaces. In this paper, we generalize the notion of strong proximinality and define simultaneous strong proximinality. It is proved that if W is a simultaneously approximatively compact subset of a Banach space X then W is simultaneously strongly proximinal and the converse holds if the set of all best simultaneous approximations to every bounded subset S of X from W is compact. We show that simultaneously strongly Chebyshev sets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In this section, we consider the simultaneous proximinality of τ -closed subsets in a Banach space. It was shown that a reflexive subspace or a weakly compact subset of a Banach space X is simultaneously proximinal [11,16], and a finite dimensional subspace is simultaneously approximatively compact [7]. We will show that every τ -compact subsets are τ -simultaneously approximatively compact, and we shall characterize reflexive spaces from simultaneous proximinality point of view.…”
Section: General Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…In this section, we consider the simultaneous proximinality of τ -closed subsets in a Banach space. It was shown that a reflexive subspace or a weakly compact subset of a Banach space X is simultaneously proximinal [11,16], and a finite dimensional subspace is simultaneously approximatively compact [7]. We will show that every τ -compact subsets are τ -simultaneously approximatively compact, and we shall characterize reflexive spaces from simultaneous proximinality point of view.…”
Section: General Resultsmentioning
confidence: 89%
“…Gupta and Narang [7] showed that a closed subset C of X is simultaneously approximatively compact if and only if C is simultaneously strongly proximinal and P C (A) is compact for every bounded subset A of X. When C is weakly closed, we have the following result.…”
Section: Corollary 23mentioning
confidence: 97%
See 2 more Smart Citations